1997
DOI: 10.1063/1.474352
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of cold electron attachment to SF6, CF3Br, and CCl2F2

Abstract: A new technique has been used for the measurement of electron attachment rate coefficients for the molecules, SF6, CF3Br, and CCl2F2 at temperatures between 48 and 170 K. The results demonstrate very clearly the strong effect that internal vibrational energy of the molecules has on the attachment process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 41 publications
5
54
0
Order By: Relevance
“…Use of such a target offers two substantial advantages: (i) The reaction volume is limited in spatial extent and thereby more easily permits the diagnosis and reduction of residual electric fields in the region of interest; (ii) in supersonic beams, the internal degrees of freedom of a molecule (rotation, vibration) are cooled more or less efficiently [15] and one can thereby investigate cooling effects on the electron attachment processes (which may strongly depend on the vibrational energy [1,2,[16][17][18][19]); in addition electron attachment to clusters can be studied (see, e.g., [19,20]). In the present Letter we address the first point.…”
mentioning
confidence: 99%
“…Use of such a target offers two substantial advantages: (i) The reaction volume is limited in spatial extent and thereby more easily permits the diagnosis and reduction of residual electric fields in the region of interest; (ii) in supersonic beams, the internal degrees of freedom of a molecule (rotation, vibration) are cooled more or less efficiently [15] and one can thereby investigate cooling effects on the electron attachment processes (which may strongly depend on the vibrational energy [1,2,[16][17][18][19]); in addition electron attachment to clusters can be studied (see, e.g., [19,20]). In the present Letter we address the first point.…”
mentioning
confidence: 99%
“…This lifetime is found to be insensitive to the electron energy, ⑀, over the range 0-100 meV, with an average value of 19.1Ϯ2.7 s. Le Garrec et al 17 have pointed out such a trend in the electron attachment rate coefficient by comparing their measurements performed under thermodynamical equilibrium with results from single collision techniques. In this last case, only the electron temperature ͑correlated to electron energy͒ varies, the neutral temperature remaining constant at 300 K. This was interpreted by the authors as being the result of an individual rate coefficient assigned to each vibrational state of the neutral molecule.…”
Section: Discussionmentioning
confidence: 91%
“…The electron density can be monitored easily by a Langmuir probe and the produced anions by a moveable mass spectrometer. Nitrogen was known to be very efficient at relaxing electrons towards the flow temperature [61] and was therefore used as the buffer. However, careful studies [62] have shown that, in this experiment, the electrons relax to a temperature higher than that in the flow.…”
Section: Electron Attachmentmentioning
confidence: 99%